2016
DOI: 10.18355/xl.2016.09.04.92-99
|View full text |Cite
|
Sign up to set email alerts
|

Classification of factors of foreign language phonic competence

Abstract: Researchers have been investigating the relationship between foreign language learning and its variables and attempting to systematize the factors of influence for about fifty years. However, the classifications differ in their criteria and most of them lack the systematic character. We introduce the classification of factors related to foreign language phonic competence with the emphasis on the language system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Attempting to understand the overall process of foreign language learning, researchers have investigated the relationship of language learning and different lingual (related to the language system) and extra-lingual (related to the language learning process) variables (Kralova, 2016).…”
Section: Factorsmentioning
confidence: 99%
“…Attempting to understand the overall process of foreign language learning, researchers have investigated the relationship of language learning and different lingual (related to the language system) and extra-lingual (related to the language learning process) variables (Kralova, 2016).…”
Section: Factorsmentioning
confidence: 99%
“…From the point of view of the percipient, the auditory impression of "good" or "bad" foreign language pronunciation is co-created by several subsegmental, segmental, plurisegmental and suprasegmental phonic phenomena (Kralova, 2016). Some studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Meador, Flege & MacKay, 2000), have shown that the most obvious deviations in foreign language pronunciation were eliminated after phonetic training, while closer (yet phonetically still imprecise) approximations of L2 sounds tended to persist. Minor deviations have more significant persistence, although they have less impact on speech comprehensibility (Kralova, 2016).…”
mentioning
confidence: 95%